Localized Angiokeratomas in a healthy adolescence responded to topical Timolol - Al-Khowailed, Mohammad S. (International Journal of Health Sciences, 2024)
Angiokeratoma (AK) is an uncommon vascular cutaneous illness that is characterized by benign vascular ectasias of the papillary dermis combined with papillomatosis, acanthosis, and hyperkeratosis of the epidermis. It often presents as mainly asymptomatic. Here, we present a case of a 14-year-old Saudi male who presented to the dermatology clinic with red-to-black nodules of varying sizes on the palmar and dorsal surfaces of his left hand. Upon examination, the nodules were painless with no other constitutional symptoms. Laboratory investigations were unremarkable. A 4-mm skin punch biopsy showed dilated vascular channels at the papillary dermis and corneal layer with acanthotic epidermis with granulation tissue; these findings were suggestive of AKs of Mibelli. Timolol drops were prescribed twice daily for 1 month, and the patient was seen after a month with a 90% resolution of lesions.